Traditional Chinese Medicine emotional nursing in the surgical care (中医情志护理在手术室中的应用) - CHEN Ying (陈颖); CAO Hongjing (曹红京); LI Ning (李宁); LI Jing (李静) (Association of Integrative Nursing, 2022)
Traditional Chinese Medicine (TCM) emotional nursing is a kind of psychological therapy, which is based on the theory of medical psychology, through the language, expression, posture, attitude, behavior and temperament of the nursing staff to affect and improve the patient emotional state. According to the patient's condition, appropriate psychological care is carried out to relieve the negative emotions, so as to achieve the purpose of disease prevention and treatment. (中医情志护理是一种社会心理疗法, 是根据中国医学教育心理学的理论, 通过提高护士的语言、表情、姿势、态度、行为及气质等来影响和改善患者的情绪。护士需要根据手术患者的病情情况, 给予适当的心理护理, 改善不良状态, 从而达到疾病防治的目的。)